Internet of Things (IoT) Innovation in Supporting Construction Industry Work Productivity - Yayah Sutisnawati; M Yani Syafei; Umi Narimawati (Electronic Journal of Education, Social Economics and Technology, 2025)
The development of the era that is increasingly moving towards the era of Internet of Things technology requires every aspect of life to be integrated with technology. Therefore, this study was conducted to analyze how the application of Internet of Things (IoT) technology can encourage innovation that has an impact on increasing work productivity in the construction industry sector. The method used in this study is a qualitative descriptive analysis method with a data collection method using secondary data, namely from scientific articles related to the object of research. The results of this study found that supporting skills related to the use of technology are something that must be possessed by employees, and company support in facilitating technology and employee capabilities are also driving factors in increasing employee work productivity. Therefore, the company in making one form of investment can provide technology and all forms of equipment and skills training that can support employee work productivity capacity.